Awareness of mental disorders and their risk factors - a nationwide cross-sectional survey among adults in Poland - Lewandowska, Aleksandra; Silczuk, Andrzej; Mularczyk-Tomczewska, Paulina; Duda-Zalewska, Aneta; Jankowski, Mateusz; Gujski, Mariusz (Frontiers in Psychiatry, 2025)
IntroductionCurrently, there are no nationwide cross-sectional studies on public awareness of mental disorders in Poland. This study aimed to identify factors associated with the awareness of mental disorders and their risk factors through a nationwide cross-sectional survey of adults in Poland.MethodsThis cross-sectional study was conducted between March 8 and 10, 2025, using the computer-assisted web interview (CAWI) technique. The questionnaire included questions on self-reported awareness of mental health, awareness of 9 mental disorders, and 12 mental disorder risk factors.ResultsThe study population comprised 1114 adults aged 18–96 years, with 54.7% being female. The majority of respondents (47.2%) reported a moderate level of awareness of mental disorders. Depression (82.6%) was the most recognized mental disorder among adults in Poland. Traumatic experiences in the past (76.8%) were the most commonly recognized risk factor for mental disorders, followed by genetic predisposition (64.5%) and difficulties in family relationships (64.5%). Factors significantly associated with a rather good/very good level of awareness of mental disorders included being under 60 years of age (p<0.05), living in cities with more than 20,000 residents (p<0.05), having higher education (aOR=1.77 [1.23-2.55]; p=0.002), and having a family history of mental disorders (aOR=2.69 [1.86-3.89]; p<0.001).ConclusionsThe level of awareness of mental disorders among adults in Poland is low, and significant differences in awareness were observed based on sociodemographic variables. Understanding these disparities is crucial for tailoring effective public health campaigns and informing national mental health strategies aimed at early detection, destigmatization, and equitable access to care.